Absence that calls, presence that responds. Showing emptiness, materializing enforced disappearance: affection and intimacy in two Central American documentaries - Gianni, Silvia (2020)
The article analyzes the issue of forced disappearance in Central American through the documentaries Ausencias (Absences) (2015) by Tatiana Huezo, and El cuarto de los huesos (The Room of the Bones) (2005) by Marcela Zamora. My approach emphasizes the vibrant and dynamic link that is established between those disappeared by one of the multiple forms of violence that shakes Central America, those present who wait and look for them, and the spectators who have watched for the documentaries. I approach trauma and memory by looking at the bodies, affections, emotions and intimacy of the families of the disappeared, thus expanding the range of perspectives and stories about trauma and memory. From this study, it emerges that mourning does not constitute the only affective modality with which to reflect on these aspects, but it only represents one of the modalities of the affective charge that is unleashed in the relationship between absent, present and spectators.